Aeromonas piscicola AH‐3 expresses an extracellular collagenase with cytotoxic properties. (1st March 2015) - Duarte, A.S.; Cavaleiro, E.; Pereira, C.; Merino, S.; Esteves, A.C.; Duarte, E.P.; Tomás, J.M.; Correia, A.C.
Abstract: The aim of this study was to investigate the presence and the phenotypic expression of a gene coding for a putative collagenase. This gene (AHA_0517) was identified in Aeromonas hydrophila ATCC 7966 genome and named colAh . We constructed and characterized an Aeromonas piscicola AH‐3:: colAh knockout mutant. Collagenolytic activity of the wild‐type and mutant strains was determined, demonstrating that colAh encodes for a collagenase. ColAh–collagen interaction was assayed by Far‐Western blot, and cytopathic effects were investigated in Vero cells. We demonstrated that ColAh is a gluzincin metallopeptidase (approx. 100 kDa), able to cleave and physically interact with collagen, that contributes for Aeromonas collagenolytic activity and cytotoxicity. ColAh possess the consensus HEXXH sequence and a glutamic acid as the third zinc binding positioned downstream the HEXXH motif, but has low sequence similarity and distinct domain architecture to the well‐known clostridial collagenases. In addition, these results highlight the importance of exploring new microbial collagenases that may have significant relevance for the health and biotechnological industries. Significance and Impact of the Study: Collagenases play a central role in processes where collagen digestion is needed, for example host invasion by pathogenic micro‐organisms. We identified a new collagenase from Aeromonas using an integrated in silico / in vitro strategy. This enzyme is able to bind and cleave collagen, contributes for AH‐3 cytotoxicity and shares low similarity with known bacterial collagenases. This is the first report of an enzyme belonging to the gluzincin subfamily of the M9 family of peptidases in Aeromonas . This study increases the current knowledge on collagenolytic enzymes bringing new perspectives for biotechnology/medical purposes.